PERSEPSI MASYARAKAT DAN TINGKAT KETERGANTUNGAN TERHADAP RUANG TERBUKA HIJAU DI TAMAN NUKILA KOTA TERNATE - Perdana Wama Setiadi; Sabaria Niapele; Asiah Salatalohy (Jurnal Akrab Juara, 2019)
Green open space (RTH) plays an important role in urban development, one of the functions of green open space is to maintain the ecological conditions of the city environment. This study aims to determine the perception and level of community dependence on the green open spaces of the Nukila Park in Ternate City. The research approach in this study is a quantitative descriptive approach, because this research is presented with numbers and verbal explanations. Data Collection Method used, Library Study. The library method is carried out to collect secondary data which is done by collecting relevant data from books, journals, articles, regulations related to research. Documentation. Documentation method is done to collect data. Data obtained in this study consists of primary data and secondary data. Primary data is obtained from the community and traders who visit the secondary data obtained from relevant institutions or agencies such as, City Planning Office, Data analysis in this study using interactive models